INTERNALISASI NILAI-NILAI MULTIKULTURALISME DENGAN PENDEKATAN ADITIF DALAM PEMBELAJARAN PAI DI SEKOLAH DASAR TAMAN HARAPAN - Syamsul Bahri (Universitas Islam Lamongan, 2017)
The Subject of Islamic Education (PAI) is part of the national curriculum that is considerably very appropriate to internalize the values of multiculturalism. But in the last few years PAI has not maximally implemented multiculturalism-oriented learning. This research was conducted at Taman Harapan Elementary School (SD), Malang City, that is also a private school with multi ethnic and multi religious students. The problems raised in this research are how should the values of multiculturalism be internalized in the PAI learning in Elementary School? The researcher conducted data collection through observation, interview and documentation. The results showed that Taman Harapan elementary school strongly supports in implementing the values of multiculturalism in the school. The PAI learning in Taman Harapan elementary school has implemented the internalization of multicultural values to its students by incorporating it in the learning curriculum (RPP), namely the Competence Standards, Basic Competencies, and Indicators of Learning Achievement. The values of multiculturalism are integrated in the PAI learning such as tolerance, equality, and cooperation.Keywords: Internalization, multiculturalism, PAI, Taman Harapan Elementary School